Aspectos da constituição de uma criança surda pela fala do ouvinte: entre traços e significantes - Lieber, Sofia Nery (2015)
This research project aims to describe and to discuss the process of subjective constitution of a deaf child by a speaking listener, in case the mother. The theoretical explanations articulates together the fields of Speech therapy, Psychoanalysis and Linguistics. The method is supported by analysis of videographic materials and transcripts of these interactions between a hearing mother and her deaf daughter, during the process of language acquisition and consequently of the subjective constitution of the child. It is intended that the research will allow launching clarifications and inputs on how is the process of constitution of a subject, in the absence of hearing and speaking skills. The demands of the deaf child, the mother responds orally, putting her in a listener place and maintaining her discursive position during the interactions. This enables the child to change discursive positions in the language structure, from somebody that yet does not speak to a speaking subject, as it occurs with hearing children